COSMIC RAY INTENSITY VARIATIONS DURING 1961 - SANDSTROM,A.E.; DYRING,E. (1962)
The note consists mainly of tables of the first and second harmonics of the daily variation recorded during 1961 in Uppsala and Kiruna. The yearly mean daily variations are illustrated by clock diagrams. Only a few prominent Forbush decreases followed by cosmic ray storms were recorded during 1961. Diagrams illustrate the intensity variations in per cent of a normal counting rate. One section and a couple of diagrams are devoted to the solar flare effects during July 1960. (Author)